Evidence for a Griffiths Phase to Cluster Spin Glass Transition in the La2/3Sr1/3(Mn1‐3xAl2xTix)O3 System - Ruie Lu; Yuanchao Ji; Yu Wang; Xiaoqin Ke; Fanghua Tian; Chao Zhou; Yin Zhang; Chang Liu; Sen Yang; Xiaobing Ren; Xiaoping Song (Advanced Science)
Abstract The presence of Griffiths phase to cluster spin glass transition has theoretically been predicted in both classical and quantum systems. However, its detection in a classical system has been lacking for decades, which hinders a complete understanding of the relationship between the Griffiths phase and cluster spin glass. Here, the experimental discovery of the Griffiths phase to cluster spin glass transition is reported in a classical magnetic system, diluted ferromagnets La2/3Sr1/3(Mn1‐3xAl2xTix)O3 (0 ≤ x ≤ 0.12). The phase diagram of the system shows a transition from the Griffiths phase into a ferromagnetic state in the low disorder concentration range (0.01 < x ≤ 0.09). In the high disorder concentration range (0.09 < x ≤ 0.12), a Griffiths phase to cluster spin glass transition is identified, which nicely matches that of disordered quantum systems. Moreover, the Griffiths phase is essentially an unfrozen cluster spin glass with partially broken ergodicity is demonstrated experimentally. These findings serve as crucial experimental references for understanding the glassy phenomena in disordered magnets, facilitating future exploration of their unique properties and functionalities.